Population Pharmacokinetics of Danofloxacin in Yellow River Carp (Cyprinus carpio haematopterus) After One Single Oral Dose - Song, Zhe-Wen; Yang, Fang; Dai, Yan; Zhang, Chao-Shuo; Shao, Hao-Tian; Wang, Han; Ma, Kai-Li; Li, Ze-En; Yang, Fan (Frontiers in Veterinary Science, 2022)
This study aimed to determine the population pharmacokinetics of danofloxacin in healthy Yellow River carp (Cyprinus carpio haematoperus) after single oral administration at 10 mg/kg body weight (BW). A sparse sampling was applied in this study, and plasma samples were randomly collected from the tail veins of six carp at 0.25, 0.5, 1, 2, 4, 6, 8, 12, 16, 24, 36, 48, 72, 96, 120 and 144 hours after administration. A maximum of four plasma samples was collected from each carp. Then the concentrations of danofloxacin in plasma samples were determined through an HPLC method. Danofloxacin could be quantified in plasma up to 122 hours after administration. The corresponding population pharmacokinetic modeling was developed according to the nonlinear mixed effect method, including covariate and covariance models to explain some variations from unknown sources and improve the prediction ability. On the premise of sparse sampling, the typical values of the population (fixed effect) and inter-individual variation (random effect) were described by the current population pharmacokinetic model. The estimated typical values and coefficient of variation between individuals (CV%) of absorption rate constant (tvKa), apparent distribution volume (tvV) and clearance (tvCL) were 2.48 h–1 and 0.203%, 47.8 L/kg and 8.40%, 0.694 L/h/kg and 4.35%, respectively. The current danofloxacin oral dosing (10 mg/kg BW) can provide suitable plasma concentrations to inhibit those pathogens with MIC values below 0.016 μg/mL based on the calculated PK/PD indices of AUC/MIC or Cmax/MIC. Further studies are still needed to determine the in vitro and in vivo antibacterial efficacy of danofloxacin against pathogens isolated from Yellow River carp and finally draw a reasonable dosing regimen.